The bioenergetics of world class cycling - Jeukendrup, A. E.; Craig, N. P.; Hawley, J. A. (Journal of Science and Medicine in Sport, 2000)
Professional cycle racing is one of the most demanding of all sports combining extremes of exercise duration, intensity and frequency. Riders are required to perform on a variety of surfaces (track, road, cross-country, mountain), terrains (level, uphill and downhill) and race situations (criterions, sprints, time trials, mass-start road races) in events ranging in duration from 10 s to 3 wk stage races covering 200 m to 4,000 km. Furthermore, professional road cyclists typically have approximately 100 race d/yr. Because of the diversity of cycle races, there are vastly different physiological demands associated with the various events. Until recently there was little information on the demands of professional cycling during training or competition. However, with the advent of reliable, valid bicycle crank dynanometers, it is now possible to quantify real-time power output, cadence and speed during a variety of track and road cycling races. This article provides novel data on the physiological demands of professional and world-class amateur cyclists and characterises some of the physiological attributes necessary for success in cycling at the elite level.